Pattern ERGs suggest a possible retinal contribution to the visual acuity loss in acute optic neuritis - Kleerekooper, I.; Del Porto, L.; Dell’Arti, L.; Guajardo, J.; Leo, S.; Robson, A. G.; Trip, S. A.; Petzold, A.; Plant, G. T.; Holder, G. E. (Documenta ophthalmologica, 2022)
Purpose Macular involvement in optic neuritis (ON) is well-recognised but poorly understood and may be of clinical relevance. This study explores macular structure–function correlates in acute ON. Methods This cross-sectional cohort study recruited ON patients within 14 days of symptom onset. Subjects underwent pattern electroretinography (PERG), pattern visual evoked potentials (PVEP) and optical coherence tomography (OCT) imaging. PERG P50 and N95 components were correlated with OCT data. Results Twenty-six individuals with ON were recruited, comprising eleven multiple sclerosis (MS-ON), six myelin oligodendrocyte glycoprotein associated (MOG-ON) and nine with isolated ON. These were compared with 28 healthy controls. PVEPs were undetectable in 11 (42%) of individuals with ON. When detectable, PVEP P100 was delayed (median 136 ms range 110–173 ms) and amplitude reduced (median 6 μV, range 3–14 μV) in ON compared with controls (both p < 0.001). PERG P50 component amplitudes, largely reflecting macular function, were reduced in affected eyes (median 2.3 μV; range 0.8–5.0 μV) compared with controls (3.3 μV; range 2.8–5.7 μV) and compared with fellow eyes ( p < 0.001). The N95:P50 ratio was below the reference range in the affected eyes of five patients. Eight cases (32%) had subnormal P50 amplitudes (< 2.0 μV), and these patients had poorer visual acuity ( p = 0.020). P50 amplitudes were positively correlated with an increase in inner nuclear layer thickness ( r s = 0.36; p = 0.009) and macular ganglion cell and inner plexiform layer (mGCIPL) thickness ( r s = 0.44, p = 0.022). Conclusion PERG P50 component reduction reveals dysfunction of inner macular layers in acute ON and correlates with structural alterations on OCT. These early macular pathologic processes are likely to contribute to the visual loss.